Effect of population density on oviposition, development, and survival of Alloeocranum biannulipes (Hemiptera: Reduviidae) preying on Dinoderus porcellus (Coleoptera: Bostrichidae) - Yêyinou Laura Estelle Loko; Joelle Toffa; Dieudonné Martin Gavoedo; Sahayaraj Kitherian; Azize Orobiyi; Manuele Tamò (Journal of Basic and Applied Zoology, 2022)
Abstract Background Alloeocranum biannulipes Montr. and Sign.(Hemiptera: Reduviidae) is a predator present in stored yam chips and a promising biological control agent against Dinoderus porcellus Lesne (Coleoptera: Bostrichidae). Numerical responses of A. biannulipes to different densities (1, 2, 4, 6, and 8) of D. porcellus larvae were evaluated under ambient laboratory conditions (T°: 25 ± 2 °C; RH: 75–80%; photoperiod 12:12 h (L/D)). The number of consumed prey, duration of pre-oviposition and oviposition, number of eggs laid, pre-imaginal development times and mortality rate of the predator were recorded. Results The results revealed that A. biannulipes females preying on the highest larval density of D. porcellus (8) presented the highest predation rate (4.34 ± 0.18 larvae/predator/day), shortest pre-oviposition period (11.01 ± 0.57 days) and the highest oviposition period (15.83 ± 1.02 days). The daily number of eggs laid by A. biannulipes female (y) as a function of the number of D. porcellus larvae consumed (x) was modelled by the equation y = 0.158x 2 – 0.4073x + 3.8151 (R 2 = 0.571). The efficiency of prey conversion into eggs of A. biannulipes females decreased with increased prey density. The prey density did not affect the hatching rate of A. biannulipes eggs and the pre-imaginal development times. However, A. biannulipes nymphs fed with more (2 to 8) D. porcellus showed a significantly higher survival rate than those fed with a single larva. Conclusions The positive numerical response of A. biannulipes suggests that this predator could play a key role in biological control program against D. porcellus.